Digital fabrication of cultural heritage artwork replicas. In the search for resilience and socio-cultural commitment. (December 2019) - Merchán, M.J.; Merchán, P.; Salamanca, S.; Pérez, E.; Nogales, T.
Abstract: The traditional approach for physical reproduction in Cultural Heritage requires the production of moulds on the very surface of the original artwork in an invasive, manual and usually time-consuming process that is intensely influenced by the complexity of the piece to be reproduced. The difficulties increase when changing the size of the copy is needed. But producing replicas is a necessity, mostly when it comes to mounting exhibitions within interpretive centres. The educational role of such institutions is beyond doubt. Furthermore, they have also become major drivers of social inclusion of at-risk groups. So, having perfect copies of archaeological remains without damaging them is a challenge that technology has been facing for the last years. This paper describes a procedure to obtain exact replicas of classical statues that reduces their manipulation, thus preventing them for further damages, which was applied to two Roman marble sculptures of Medellín (Badajoz, Spain). Highlights: Interpretive centres foster deep learning and social cohesion. Digital fabrication proves that far surpasses traditional methods when replicating cultural heritage assets. 3D digitization guarantees the resilience of the Antiquity.